AB0582 Improvements in health-related quality of life (HRQOL) in patients with rheumatoid arthritis (RA) receiving secukinumab: Results of a dose-finding study. (23rd January 2014) - Strand, V.; Genovese, M.; Mallya, U.; Richards, H.; Mpofu, S.
Abstract : Background: Interleukin (IL)-17A is a key inflammatory mediator in pathogenesis of RA. Secukinumab is a fully human monoclonal antibody that selectively binds and neutralizes IL-17A. Objectives: To assess the effects of secukinumab administration on patient reported HRQoL by SF-36 v2, a secondary outcome in a phase 2 randomized controlled trial [RCT]. Methods: Patients (n=237, ≥18 yrs) failing methotrexate were randomized equally to receive monthly s.c. injections of secukinumab 25mg, 75mg, 150mg, 300mg or placebo. Clinical (ACR 20) and HRQoL responses were assessed at weeks 0, 2, 4, 8, 12 and 16, and SF-6D scores were derived based on mean changes across all 8 domains of SF-36v2 1 . Data were analyzed using descriptive statistics and mean changes ≥ minimum clinically important differences [MCID]. Results: Baseline PCS (physical component scores) and physical domain scores were low across all treatment groups: ≥1.5 standard deviations (SD) and 26 – 40 points less than Age/Gender matched norms; MCS (mental component scores) approximately 1 SD < norms, reflecting the large impact of active RA on HRQoL [Table]. ACR 20 responders at week 16 in secukinumab 75–300mg treatment groups exceeded 25mg and placebo 2 . In view of small sample sizes, although changes from baseline at week 16 in summary and domain scores of SF-36v2 were not statistically significant, improvements in PCS and MCS scores and 7 of 8 domains in 75mg and all 8 domains in 150mg treatment groups met or exceeded MCID and as well SF-6D well exceeded MID =0.041 3 . Mean changes in 300mg were of less magnitude than 75 or 150mg but ≥ MCID in PCS and 3 of 8 domain scores. Improvements with 25mg were not different from placebo, consistent with earlier findings of a "no effect" dose 2 . Conclusions: A dose response in reported improvements in HRQoL was evident with 75mg and 150mg, exceeding those observed with 25mg, 300mg and placebo. From an HRQoL perspective, these findings support the selection of secukinumab 75mg and 150mg doses for future phase 3 RCTs in RA. References: Strand V et al. Ann Rheum Dis 2009; 68:1800-04. Genovese M et al. Arthritis & Rheum 2010; 62:3842. Ara R, Brazier J. Value in Health 2009; 12:346-53. Disclosure of Interest: V. Strand Consultant for: Novartis Pharmaceuticals Corporation, M. Genovese Grant/Research support from: Novartis Pharmaceuticals Corporation, U. Mallya Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, H. Richards Employee of: Novartis Pharma AG, S. Mpofu Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG